Microglia Pyroptosis-Derived IL-18 Drives White Matter Injury in Developing Brain following Hypothermic Hypoxia-Ischemia - Hongtong Chen; Shengyu Jin; Mingdong Liu; Yifan Zhu; Liren Zhang; Cong Li; Peng Liu; Xiaoping Tong; Zhongqun Zhu (Neuroscience Bulletin, 2026)
Hypothermia is widely acknowledged to exert protective effects against cerebral hypoxic-ischemic injury. Despite the neuroprotective effects of hypothermia, the developing brain remains vulnerable to white matter injury (WMI) during hypothermic hypoxia-ischemia, potentially disrupting neurodevelopment and leading to long-term neurological deficits. However, the mechanisms underlying WMI and effective therapeutic strategies following hypothermic hypoxia-ischemia in the developing brain are not well understood. Our study demonstrates that microglia experience pyroptosis following hypothermic hypoxia-ischemia. The release of interleukin 18 (IL-18) derived from pyroptotic microglia induces mature oligodendrocyte death and axonal demyelination, resulting in WMI. Pharmacological inhibition of pyroptosis with disulfiram (DSF) significantly alleviates WMI in vitro and in vivo . These findings highlight microglia pyroptosis as a potential therapeutic target to prevent neurodevelopmental impairment in the developing brain following hypothermic hypoxia-ischemia.